Analisis Implementasi E-Katalog Terhadap Perkembangan UMKM di Kota Medan dalam Mendukung Kemajuan Ekonomi Syariah - Fitri Diani; Fauzi Arif Lubis (ITB AAS INDONESIA Surakarta, 2022)
Indonesia has been classified as a developing country because its economic growth is accelerating both materially and non-materially. Indonesia's economy continues to grow and develop, necessitating increased government supervision. When these requirements are satisfied through the acquisition of commodities or services. The Medan City Government is now launching a Local E-Catalog program for workers in MSME businesses (Micro, Small and Medium Enterprises). The Local E-Catalog Program was established to aid in the recovery of the city of Medan's economy following the Covid-19 outbreak. The researcher is referring to the Medan City Government, which is actually the Medan Marelan District Government. Three MSME entrepreneurs have been added to the Local E-Catalog, which is quite a number given the District's population of MSME entrepreneurs. This study employs a kind of qualitative research known as interaction analysis, which entails reporting and analyzing encounters. Interviews, observation, and documentation are used to acquire data. The research findings indicate that both MSME enterprises that participate in the Medan Local E-Catalog and MSME business players that do not participate in the Local E-Catalog have benefited from the PMK Kasi work program, specifically the creation of the Medan Marelan Berkah MSME Cooperative. This shows that MSMEs in this sub-district do not or have not utilized existing technology and innovated well in line with the times. Certainly not in accordance with the advice of Allah SWT, where He ordered his people to always be creative and innovate in various activities.